2004
DOI: 10.1002/adsc.200404203
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Heck Reaction

Abstract: The asymmetric Heck reaction is a powerful method for the synthesis of both tertiary and quaternary chiral carbon centers, with an enantiomeric excess often greater than 80%, and in some cases much higher (up to 99% ee). A variety of carbocyclic and heterocyclic systems can be constructed, including spirocyclic systems. The scope of the reaction with respect to the product alkene isomerization is somewhat limited by problems of regioselectivity, however, these problems are surmountable, and a new generation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
97
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(102 citation statements)
references
References 139 publications
1
97
0
2
Order By: Relevance
“…Potentially, this modification could be useful for large-scale synthesis because 11 is much cheaper and easier to handle than methyl isocyanate. [19] Enantioselective Heck-cyanation process: A number of palladium-catalyzed enantioselective Heck cyclizations and oligA C H T U N G T R E N N U N G ocyclizations have been developed since the seminal contributions of the groups of Shibasaki [20] and Overman, respectively. [21] Whereas examples of enantioselective Heck cyclization-anion capture of resulting p-allyl-Pd II complexes are known, [22] to the best of our knowledge, the corresponding enantioselective Heck cyclization-anion capture of the resulting s-alkyl-Pd II complex is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially, this modification could be useful for large-scale synthesis because 11 is much cheaper and easier to handle than methyl isocyanate. [19] Enantioselective Heck-cyanation process: A number of palladium-catalyzed enantioselective Heck cyclizations and oligA C H T U N G T R E N N U N G ocyclizations have been developed since the seminal contributions of the groups of Shibasaki [20] and Overman, respectively. [21] Whereas examples of enantioselective Heck cyclization-anion capture of resulting p-allyl-Pd II complexes are known, [22] to the best of our knowledge, the corresponding enantioselective Heck cyclization-anion capture of the resulting s-alkyl-Pd II complex is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Ligands at palladium play a different role depending on the application. While the ligation is crucially important for enantioselective variants of the Heck reaction [2] or activation of otherwise unreactive aryl chlorides, [3] it often tends to deteriorate the desired coupling, causes side reactions and deactivates the catalyst, [4] in particular, when aryl iodides are used as substrates.[5] From this standpoint, it is of no surprise that the fastest versions of Heck reaction known so far are described for ligand-free systems containing free halides (Cl À or Br À added as quaternary ammonium salts) which are believed to stabilize Pd(0)-species.[1d]Later on, it was shown that intermediary Pd nanoparticles as colloids are likely to be the true catalytic species in such systems. [6] Owing to the recent advancements in the mechanistic study and design of robust and efficient low Pd-loading systems, [7] the ligand-free Heck reaction became an emerging trend with particular promise for industrial applications.…”
mentioning
confidence: 99%
“…NMR spectra were recorded on Varian GEMINI 300 spectrometer with CHCl 3 (7.26 ppm for 5,156.5,141.2,135.3,132.8,129.6,121.8,116.2,110.6,105.3,72.9,66.2,25.6,25.5;IR (neat) 156.6, 141.2, 135.0, 132.3, 129.9, 121.4, 116.3, 110.8, 105.2, 72.8, 67.0, 25.9, 25.8, 25.5, 18.4, -5.19, -5.24 159.7,156.5,141.7,135.9,135.8,134.8,134.7,134.1,133.9,129.4,129.3,128.6,127.4,127.3,121.4,115.8,110.8,105.0,74.7,67.6,72.1,26.0,25.8,25.6,19.4,18.4,IR (neat) 9,156.6,141.5,139.4,136.0,135.9,135.5,134.9,133.9,133.9,129.5,129.4,127.9,127.4,121.5,…”
Section: Methodsmentioning
confidence: 99%